Controllable synthesis of hierarchical ball-in-ball hollow microspheres for a high performance layered Li-rich oxide cathode material. Issue 19 (2nd May 2017) - Yu, Fu-Da; Que, Lan-Fang; Wang, Zhen-Bo; Xue, Yuan; Zhang, Yin; Liu, Bao-Sheng; Gu, Da-Ming
Abstract : Novel hierarchical ball-in-ball hollow Li-rich microspheres with a multi-elemental composition are reported as a high performance cathode material for Li-ion batteries with excellent rate capability and superior cycle stability. Abstract : Layered Li-rich oxide (LLRO) is an attractive candidate for high-energy-density and high-voltage cathode material for next generation lithium ion batteries because of its high specific capacity and low cost. There still remain challenges in simultaneously achieving a multi-functional structure and composition in a LLRO, to achieve better electrochemical performance. Here we report a controllable co-precipitation and calcination method to synthesize LLRO by tuning the crystal nucleation, growth and heterogeneous contraction processes. The resultant LLRO adopts a hierarchical ball-in-ball hollow structure consisting of uniform multi-elemental (Mn–Ni–Co) primary nanocrystals, and exhibits high reversible capacity, remarkable cycle stability and superior rate performance. As a result, the resultant LLRO presents a high capacity of 193 mA h g −1 at 3C (a current density of 750 mA g −1 ) with a capacity retention of 87.6% after 400 cycles, and exhibits a capacity of 132 mA h g −1 at a high rate of 10C; moreover, it displays a quite slow voltage decay of ∼240 mV and a high energy density of 668 W h kg −1 after 200 cycles at 1C. The excellent electrochemical performance can be attributed to the combined merits of the multi-functional structure and composition, wherein the hierarchical hollow architecture facilitates efficient electron/ion transport and high structural stability, while multi-elemental components offer high reversible capacity.